Women organising in fragility and conflict: lessons from the #BringBackOurGirls movement, Nigeria. Issue 2 (2nd September 2021) - Atela, Martin; Ojebode, Ayobami; Makokha, Racheal; Otieno, Marion; Aina, Tade
ABSTRACT: Public protests, including women-led struggles, are increasingly gaining a foothold in many parts of the world in response to multiple crises and growing exclusion, in a context of fragility. In the global South, most public protests involve temporary, informal coalitions where people come together and participate in a one-off event. The fluid nature of political space makes sustaining protests elusive because of protest fatigue. Yet, the #BringBackOurGirls (#BBOG), a women-led movement, headed a long-term protest that focused on the rights of the girl child to education – a direct response to Boko Haram's gendered terror tactics, in which girls were abducted, forced to abandon school, and get married. This article examines when and how movements crystallise into long-term programmes of action in fragile and conflict-affected societies where state–society relations are weak and government is considered to be unresponsive. We use the case of the #BBOG movement, one of Nigeria's intense social media-driven and women-led action, to examine the mix of pressures it faced, its characteristics, and strategies in situations of fragility, conflict, and closed political spaces. We identify four key strategies that the #BBOG has deployed to keep members coming, garner international support and sympathy, keep pressure on the elite in a safe manner for the movement members, and ensure an independent funding regime for durability and impact. This article finds that #BBOG was able to navigate fragility and the closing civic space in Nigeria by challenging the failure of government to address insecurity in the country, transcending societal barriers including gender, religion, and political class, transnationalising their movement, self-funding, and using social media strategically.